Regulation of Adaptive Thermogenesis and Browning by Prebiotics and Postbiotics - Reynés, Bàrbara; Palou, Mariona; Rodríguez, Ana M.; Palou, Andreu (Frontiers in Physiology, 2019)
Abstract Prebiotics are non-digestible food components able to modify host microbiota towards a healthy profile, concomitantly conferring general beneficial health effects. Numerous research works have provided wide evidence regarding the effects of prebiotics on the protection against different detrimental phenotypes related to cancer, immunity, and features of the metabolic syndrome, among others. Nonetheless, one topic less studied so far, but relevant, relates to the connection between prebiotics and energy metabolism regulation (and the prevention or treatment of obesity), especially by means of their impact on adaptive (non-shivering) thermogenesis in brown adipose tissue (BAT) and in the browning of white adipose tissue (WAT). In the present review, a key link between prebiotics and the regulation of adaptive thermogenesis and lipid metabolism (in both BAT and WAT) is proposed, thus connecting prebiotic consumption, microbiota selection (especially gut microbiota), production of microbiota metabolites, and the regulation of energy metabolism in adipose tissue, particularly regarding the effects on browning promotion, or on BAT recruitment. In this sense, various types of prebiotics, from complex carbohydrates to phenolic compounds, have been studied regarding their microbiota-modulating role and their effects on crucial tissues for energy metabolism, including adipose tissue. Other studies have analysed the effects of the main metabolites produced by selected microbiota on the improvement of metabolism, such as short chain fatty acids and secondary bile acids. Here, we focus on state-of-the-art evidence to demonstrate that different prebiotics can have an impact on energy metabolism and the prevention or treatment of obesity (and its associated disorders) by inducing or regulating adaptive thermogenic capacity in WAT and/or BAT, through modulation of microbiota and their derived metabolites.